PERBEDAAN METODE PEMBELAJARAN PQRST (PREVIEW, QUESTION, READ, SUMMARIZE, TEST) DENGAN METODE PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW) TERHADAP KEMAMPUAN MEMBACA CERPEN - Sartika, Rina; Rahayu Fitri (CV. Kalimasada Group, 2023)
This research is motivated by the following problems. First, students do not understand the content of short stories whose language is too high so they have difficulty reading short stories. Second, students have difficulty understanding the material because sometimes teachers explain the material too quickly and concisely. This research aims to describe the differences in the use of the PQRST (Preview, Question, Read, Summarize, Test) method and the PQ4R (Preview, Question, Read, Reflect, Recite, Review) method on the short story reading skills of class XI students at Semen Padang High School.This type of research is quantitative research using experimental methods. The design of this research is one group pretest-posttest design. The population of this study were all class XI students of Semen Padang High School. The sample in this research was 27 class XI students of Semen Padang High School. The data in this study are scores using the PQRST method for class XI students at Semen Padang High School and scores using the PQ4R method (Preview, Question, Read, Reflect, Recite, Review) for class XI high school students Semen Padang.The results of this research can be concluded as follows. First, the short story reading skills after using the PQRST method for class Second the short story reading skills after using the PQ4R (Preview, Question, Read, Reflect, Recite, Review) method for class In other words there is a difference in the use of the PQRST method and the PQ4R method on the short story reading skills of class XI